SEJARAH TEORI KEWIRAUSAHAAN: DARI SAUDAGAR SAMPAI KE TEKNOPRENUR STARTUP - Mintardjo, Christoffel M. O.; Ogi, Imelda W.; Kawung, George M. V.; Raintung, Michael Ch. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
Entrepreneurial activities have existed since the advent of human civilization, making this activity one of the oldest professions of humankind. Entrepreneurial thought as a scientific concept began in the middle of the 15th century two decades before the advent of economic theory from Adam Smith. The development of entrepreneurship theory continues to grow until the era of technology-based entrepreneurship in the third millennium. This paper aims to explore the historical chronology of the development of entrepreneurship theory in general.Entrepreneurship theory, entrepreneurship history, though, research, activity